SPEECH ACT AND POLITENESS STRATEGY OF RASULULLAH MUHAMMAD SAW ON THE BOOK OF HADITH BUKHARI - Wilda Zaki Alhamidi; Dwi Purnanto; Djatmika Djatmika (Universitas Muhammadiyah Semarang, 2019)
This research reviews prophet Muhammad SAW utterances when talking to people who had different paradigms from him. The data used in this research are the conversations of prophet Muhammad to non-moslim in book hadith of Bukhari. This research is qualitative study and to analyze the data is used heuristics method. The result shows that from 34 Rasulullah Muhammad’s speeches against non muslim people are found 3 types of speech acts, those are 16 directive speech acts, 17 assertive and 1 rogative. Moreover the most dominant politeness that arises is negative politeness. It happened because negative politeness is used to protect negative face that was used for a social relationship between speaker and hearer. Furthermore, Off the Record strategy is to be the most dominant in asertive type because a speaker (Prophet Muhammad) used a communication strategy by not stating directive speech directly to the non muslim as the hearer.